PANDANGAN SASTRAWATI TERHADAP IBU RUMAH TANGGA DALAM KARYA SASTRANYA - Wahyudi Siswanto (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2014)
How art views to the existence of housewife? This matter draws the views of belles-lettres in their personal mirror. This qualitative study is focused to see (1) profile activity of housewife, (2) profile access and access housewife control, and (3) factor analysis causing differences of woman and men at profile and access. Data of this study is art view of housewife in its belles-lettres. Source of the data is year art short story 1990-2005, including “Perempuan”, “Hati”, dan “Cincin Kawin”. The study revealed that there are two profile activities of housewife: labouring in domestic and public sectors. In the  access aspect, the activity is limited and in the control aspect, women are not free of control. Factor analysis indicating role, access, and housewife control according to art in its belles-lettres consists of traditional woman and hateful woman of man as a result of much inequitable treatment since childhood to adult